Rekomendasi Waktu Rem Minimum untuk Uji Layak Jalan Sepeda Motor Berdasarkan Ketebalan Brake Pad dengan Metode Taguchi - Siahaan, Ian Hardianto; Jonoadji, Ninuk; Welianto, Andre (Jurnal Teknik Mesin, 2024)
One of the main factors ensuring the safety of motor vehicle riders is their braking system. This system plays a crucial role in slowing down or stopping the vehicle. The efficiency of braking in disc brake systems is influenced by various aspects, one of which is the level of wear on the brake pads. When brake pads wear out, their thickness decreases, which can affect braking performance. The thinner the brake pads, the longer the stopping time required, which can increase the risk of accidents. This study aims to educate motorcycle users, as many still use brake pads even when their thickness has reached the minimum limit of 2-3 mm. The methodology used in this research is a stationary test that varies the thickness of worn brake pads, specifically at 2 mm, 4 mm, and 6 mm conditions. Subsequently, the three brake pads were tested at safe speed limits, ranging from 20, 40, to 60 km/h, with normal braking loads of 4 kg, 5 kg, and 6 kg. The conclusion indicates that the effective stopping time for motorcycle brake pads should be between 1.07 and 1.13 seconds, showing that braking performance is still adequate at a brake pad thickness of 2-3 mm to prevent the risk of accidents.